An Analysis of XBRL Adoption Towards Systemic Risk of Financial Institutions Listed in NYSE - Andreas Suwardi; Valentina Tohang (Australasian Accounting, Business and Finance Journal, 2017)
This research aims to test the impact of the mandatory adoption of XBRL towards the systemic risk of American financial institutions listed in New York Stock Exchange (NYSE) by utilizing 45 NYSE listed financial institutions for the time period of 2007-2012. The measure of systemic risk is based on SRisk by Acharya et al. (2012) which is available in the NYU Stern V-Lab. XBRL is a dummy variable, in which 0 represents a pre XBRL adoption period (2007-2008) while 1 represents an XBRL reporting environment (2011-2012). It is further interacted with Corporate Governance, which is measured using an index developed by Brown & Caylor (2006). The result proves that XBRL do not significantly impact systemic risk of financial institutions listed in NYSE. The findings have been determined after having controlled firm size, capital ratio, leverage ratio and performance.
Keywords: Systemic Risk; XBRL; Corporate Governance; Market Discipline; Financial Institution; Disclosure; NYSE; Risk Taking